2020
DOI: 10.1021/acsami.0c04572
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cell Surface Structure and Chitin–Protein Co-assembly Determine Fiber Architecture in the Locust Cuticle

Abstract: The geometrical similarity of helicoidal fiber arrangement in many biological fibrous extracellular matrices, such as bone, plant cell wall, or arthropod cuticle, to that of cholesteric liquid mesophases has led to the hypothesis that they may form passively through a mesophase precursor rather than by direct cellular control. In search of direct evidence to support or refute this hypothesis, here, we studied the process of cuticle formation in the tibia of the migratory locust, Locusta migratoria, where daily… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In the locust Locusta migratoria, chitin orientation is under circadian control, with unidirectional fibers forming during the day and helicoidal (left-twisting) fibers at night 50 . Day microvilli are oriented such that chitin fibers are secreted into the assembly zone in their final orientation, whereas night fibers are secreted then self-assembled into the final helicoidal structure 51 . This work suggests that fine aECM structure may be determined by the regulated interplay of templating on cellular structures and extracellular self-assembly mechanisms.…”
Section: The Aecm Of the Drosophila Melanogaster Cmentioning
confidence: 99%
“…In the locust Locusta migratoria, chitin orientation is under circadian control, with unidirectional fibers forming during the day and helicoidal (left-twisting) fibers at night 50 . Day microvilli are oriented such that chitin fibers are secreted into the assembly zone in their final orientation, whereas night fibers are secreted then self-assembled into the final helicoidal structure 51 . This work suggests that fine aECM structure may be determined by the regulated interplay of templating on cellular structures and extracellular self-assembly mechanisms.…”
Section: The Aecm Of the Drosophila Melanogaster Cmentioning
confidence: 99%
“…For spiders, the particular details of cuticle formation have not been studied yet, but a lot more is already known for the assembly of insect cuticle. The formation of parallel and helicoidal fibre arrays in locusts' cuticles involves a self-organization process dictated by the boundary conditions determined by the cells and driven by co-assembly of its main building blocks [104][105][106]. It will require further study in order to fully understand all the steps of this process, but this effort is likely worthwhile and may lead to new ideas that can be implemented in a sustainable synthesis of new 'smart' materials, and exquisitely tuned functional structures made from them.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-scale structuring a material and structural grading may be well used to build lightweight structures, thereby reducing the energy costs for their transport, and potentially also the energy needed for their function without compromising their mechanical properties. On the contrary, in addition to rendering these materials more sustainable, mesoscale structuring of materials, including for example steel and concrete, two of the most important CO 2 emitter industries, has already been shown to lead to improvement of their mechanical properties such as strength and damage resistance, as seen in biological materials [101][102][103][104][105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations of different biological disciplines concluded that the high performance of natural chitin matrices relies on their specialized structures, the perfect packaging of the chitin/chitosan chains into long fibers that must assemble into complex architectures [ 109 ]. A key role lies in the molecular mechanisms, namely the genes coding for the key proteins and enzymes that establish natural chitin matrices, mature them, and degrade them without preventing newly formed matrices from keeping epithelial barriers [ 110 , 111 , 112 ].…”
Section: Using the Natural Toolbox To Improve The Quality Of Syntheti...mentioning
confidence: 99%
“…The latter can form initial chitin fibrils in a self-assembly process [ 111 ]. Dynamic apical cell surface structures (microvilli) can determine the boundary conditions for chitin-fiber self-assembly [ 112 ]. However, the synthesis and initial self-assembly of chitin polymers are not enough to form chitin matrices with defined architecture and properties.…”
Section: The Molecular Toolbox For Natural Chitin Matrix Productionmentioning
confidence: 99%